Thymine DNA Glycosylase Can Rapidly Excise 5-Formylcytosine and 5-Carboxylcytosine: POTENTIAL IMPLICATIONS FOR ACTIVE DEMETHYLATION OF CpG SITES - Maiti, Atanu (American Society for Biochemistry and Molecular Biology, 2011)
Thymine DNA glycosylase (TDG) excises T from G·T mispairs and is thought to initiate base excision repair (BER) of deaminated 5-methylcytosine (mC). Recent studies show that TDG, including its glycosylase activity, is essential for active DNA demethylation and embryonic development. These and other findings suggest that active demethylation could involve mC deamination by a deaminase, giving a G·T mispair followed by TDG-initiated BER. An alternative proposal is that demethylation could involve iterative oxidation of mC to 5-hydroxymethylcytosine (hmC) and then to 5-formylcytosine (fC) and 5-carboxylcytosine (caC), mediated by a Tet (ten eleven translocation) enzyme, with conversion of caC to C by a putative decarboxylase. Our previous studies suggest that TDG could excise fC and caC from DNA, which could provide another potential demethylation mechanism. We show here that TDG rapidly removes fC, with higher activity than for G·T mispairs, and has substantial caC excision activity, yet it cannot remove hmC. TDG excision of fC and caC, oxidation products of mC, is consistent with its strong specificity for excising bases from a CpG context. Our findings reveal a remarkable new aspect of specificity for TDG, inform its catalytic mechanism, and suggest that TDG could protect against fC-induced mutagenesis. The results also suggest a new potential mechanism for active DNA demethylation, involving TDG excision of Tet-produced fC (or caC) and subsequent BER. Such a mechanism obviates the need for a decarboxylase and is consistent with findings that TDG glycosylase activity is essential for active demethylation and embryonic development, as are mechanisms involving TDG excision of deaminated mC or hmC.